Uterine arteriovenous malformation: US, color Doppler US and MRI findings (case report) - Murat, Ayşe; Boztosun, Yasemin; Ogur, Erkin (My University, 2004)
Uterine arteriovenous malformations are rare but life threatening lesions. Sixty nine-year old, multiparous, postmenopausal patient complained of intermittent vaginal hemorrhage for 4 years. Serum beta-HCG level of the patient who had no history of uterine curettage or pelvic operation was normal. Noninvasive diagnosis of arteriovenous malformations with congenital or acquired etiology can be made by color Doppler ultrasonography and MRI.
Uterin arteryovenöz malformasyon: US, renkli Doppler US ve MRG bulgulari.
Keywords: Aged; Arteriovenous Malformations; Diagnosis, Differential; Female; Humans; Magnetic Resonance Imaging; Ultrasonography, Doppler, Color; Uterine Hemorrhage; Uterus; aged; arteriovenous malformation; article; case report; color ultrasound flowmetry; differential diagnosis; echography; female; human; nuclear magnetic resonance imaging; pathology; uterus; uterus bleeding; vascularization